Pietras, Dawid, FSSP. 2025. Kompetencje administracyjne biskupa diecezjalnego według obowiązującej dyscypliny Kościoła łacińskiego, 243. Kraków: Wydawnictwo «scriptum». - Góralski, Wojciech (Prawo Kanoniczne, 2026)
The author addresses an issue in canonical administrative law of considerable theoretical and practical significance, as it provides guidance for the proper application of legal norms in the governance of a diocese. Examining the competences of the diocesan bishop in the administrative sphere, Fr. Pietras defines the nature of administrative activity, outlines the bishop’s responsibilities in this area, and identifies the bodies that assist him in the exercise of administrative governance. The analyses presented in the study substantiate the conclusion that administration plays a crucial role in the functioning of a diocese. Particular emphasis is placed on the pastoral dimension of ecclesiastical administration. The study is characterized by extensive reference to the scholarly literature on canonical administrative law.